A Longitudinal Investigation of the Home Literacy Environment and Shared Book Reading in Young Children with Hearing Loss - DesJardin, Jean L. (Ear Hear, 2017)
OBJECTIVES: The principle goal of this longitudinal study was to examine parent perceptions of home literacy environment (e.g., frequency of book reading, ease of book reading with child) and observed behaviors during shared book reading (SBR) interactions between parents and their children with hearing loss (HL) as compared to parents and their children with normal hearing (NH) across three time points (12-, 24-, and 36-months old). Relationships were also explored among home literacy environment factors and SBR behaviors and later language outcomes, across all three time points for parents of children with and without HL. DESIGN: Participants were a group of parents and their children with HL (N = 17) and typically developing children with NH (N = 34). Parent perceptions about the home literacy environment were captured through a questionnaire. Observed parent behaviors and their use of facilitative language techniques (FLTs) were coded during videotaped SBR interactions. Children's oral language skills were assessed using a standardized language measure at each time point. RESULTS: No significant differences emerged between groups of parents (HL and NH) in terms of perceived home literacy environment at 12 and 36 months. However, significant group differences were evident for parent perceived ease of reading to their child at 24 months. Group differences also emerged for parental SBR behaviors for literacy strategies and interactive reading at 12 months and for engagement and interactive reading at 36 months, with parents of children with HL scoring lower in all factors. No significant relationships emerged between early home literacy factors and SBR behaviors at 12 months and oral language skills at 36 months for parents of children with NH. However, significant positive relationships were evident between early home literacy environment factors at 12 months and oral language skills at 36 months for parents and their children with HL. CONCLUSIONS: Although both groups of parents increased their frequency of SBR behaviors over time, parents of children with HL may need additional support to optimize SBR experiences to better guide their toddlers and preschoolers’ language skills. Early intervention efforts that focus on SBR interactions that are mutually enjoyed and incorporate specific ways to encourage parent-child conversations will be essential as children with HL acquire language.